Fatal Outcome of Multiple Clinical Presentations of Human Herpesvirus 8–related Disease After Solid Organ Transplantation. Issue 1 (January 2016) - Vijgen, Sandrine; Wyss, Caroline; Meylan, Pascal; Bisig, Bettina; Letovanec, Igor; Manuel, Oriol; Pascual, Manuel; de Leval, Laurence
Abstract : Kaposi sarcoma is the most common human herpesvirus 8 (HHV-8)–related disease described after solid organ transplantation. Multicentric Castleman disease and hemophagocytic syndrome are other potential HHV-8–induced entities but are less frequently reported. We describe the case of a liver transplant recipient who presented with an acute febrile illness 1 year after transplantation with a rapidly fatal outcome. Autopsy revealed 3 distinct HHV-8–related entities: Kaposi sarcoma, HHV-8-associated multicentric Castleman disease with microlymphomas and a severe hemophagocytic syndrome. Retrospective serologic tests suggested that HHV-8 was likely transmitted by the seropositive donor at the time of transplantation. To our knowledge, this is the first case of copresentation of 3 clinical presentations of HHV-8–mediated human disease in the post-transplant setting. Considering the absence of systematic screening of organ donors/recipients for HHV-8 infection, HHV-8–related illness should be suspected in transplant recipients who present with acute febrile illness, systemic symptoms, lymphadenopathies, and/or multiorgan failure to rapidly document the diagnosis and provide timely an adequate treatment. Abstract : Human herpesvirus 8-related disease may manifest as Kaposi's sarcoma, multicentric Castleman disease, or hemophagocytic syndrome. A liver transplant patient developed a febrile illness with copresentation of all 3 one year after transplant and died. Autopsy studies demonstrated the infection was probably donor derived.